STUDY PROTOCOL OF A MULTI-STAGE RANDOMISED CONTROLLED STUDY FOR THE ASSESSMENT OF POSTOPERATIVE THERAPEUTIC PROCEDURES AFTER TOTAL KNEE ARTHROPLASTY - Prill R; Kirschner J; Michel S; Schulz R; Hommel H (International Journal of Physiotherapy, 2018)
Background: There continues to be a lack of evidence to support physiotherapeutic rehabilitation measures after total knee arthroplasty (TKA), especially in the area of functional test procedures, which are indispensable for assessing perioperative physiotherapeutic interventions, including their efficacy. Objective: A multi-stage randomized controlled study design is concerned with the establishment of an evidence-based perioperative physiotherapeutic treatment programme to evaluate physical functional test procedures with regard to their predictive value and the efficacy of physiotherapeutic interventions. Setting: The RCT will be realized in a medical clinic in the department of orthopaedics, sports medicine and rehabilitation.Participants: A first stage will include young, healthy subjects (Group A) and subjects who are due to undergo TKA and are then to be treated with a standard rehabilitation programme (Group B). Design: Selected promising physical functional test procedures will be tested for their reliability. Inter-tester reliability will be determined in Group A. The test-retest reliability at different perioperative timepoints will be determined in Group B. Measurements: The following test procedures will be investigated for reliability: 10-m walk test, timed up and go, three times sit to stand, the isometric maximal force of knee extension, stair climbing and the cumulative leg circumference. In addition, these test procedures will be correlated with each other and with the WOMAC and KSS for selected aspects of validity. In a second stage, the reliable test procedures will be applied to investigate selected promising physiotherapeutic interventions. Conclusions: The investigation could change perioperative assessments and physiotherapeutic treatment in patients who have undergone TKA.